Electrolyte effects on the electrochemical performance of microemulsions. (10th October 2021) - Peng, Jing; Xiao, Ye; Imel, Adam; Barth, Brian Andrew; Cantillo, Nelly M.; Nelms, K. McKensie; Zawodzinski, Thomas A.
Abstract: We report a study of the electrochemistry of Ferrocene (Fc) in a Tween®20 (polyethylene glycol (20) sorbitan monolaurate) /1-butanol/ water/Toluene (TBWT) microemulsion system, focusing on the effects of electrolyte components. Resistance and conductivity measurements are used along with Cyclic Voltammetry (CV) to characterize the effects of supporting electrolyte, such as Bu4 NBF4 and KNO3, on the electrochemical performance and transport properties of Fc. With increasing Fc-containing oil phase concentration in the microemulsion, the observed peak current density fails to increase proportionately with the Fc concentration. Adding 0.05 m Bu4 NBF4 in the oil phase significantly increases the current density, presumably by lowering the resistance of microemulsion and promoting the accessibility of Fc in the system. Moreover, increasing the aqueous phase supporting electrolyte from 0.5 m KNO3 to 1 m KNO3 does not exhibit an analogous effect. We discuss these results in the context of our working hypothesis for microemulsion organization and its implications for electron transfer to Fc.